Study On E-Procurement Implementation Effect On Performance Through An Improved Procurement Efficiency Of Construction Work In The Public Works Department Of Enrekang Regency - Affandi Nur; Hamka Naping; Erlina Pakki; Andi Reni (Cita konsultindo, 2023)
This study aims to examine effect of implementation of e-procurement on performance, through an improved procurement efficiency of construction work at the Public Works Department of Enrekang Regency. A quantitative approach with saturated sampling was employed, and the population comprised 44 respondents, which were selected from the civil servant general data. Furthermore, several tests were conducted on the collected data when it was being analyzed, they include the descriptive statistical (TCR), validity, reliability, normality, simple correlation, multiple linear regression, path analysis, and the coefficient of determination tests, as well as the F-test, and T-test. The results show e-procurement implementation has a partially significant effect on both performance and procurement efficiency, while efficiency greatly influences performance. Simultaneously, e-procurement implementation was found to have a positive significant effect on performance through procurement efficiency of construction work at the Public Works Department of Enrekang Regency. Specifically, e-procurement implementation variable (X) was able to affect performance variable (Y) through procurement efficiency variable (Z) by 54.7%. It is also worth noting that the remaining 45.3% (100% - 54.7%) can be attributed to variables other than the independent variables in the study. This means that an increase in e-procurement implementation will lead to a proportional increase in performance value through procurement efficiency